2018
DOI: 10.21873/anticanres.12297
|View full text |Cite
|
Sign up to set email alerts
|

Control of Nausea and Vomiting in Patients Receiving Anthracycline/Cyclophosphamide Chemotherapy for Breast Cancer

Abstract: Abstract. Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…Previous studies report similar levels of vomiting. [ 22 23 ] As compared to nausea, vomiting was identified more frequently in the current study although literature shows that nausea is in fact more frequently occurring,[ 22 23 24 ] further supporting the hypothesis that nausea was under-reported.…”
Section: Discussionsupporting
confidence: 75%
“…Previous studies report similar levels of vomiting. [ 22 23 ] As compared to nausea, vomiting was identified more frequently in the current study although literature shows that nausea is in fact more frequently occurring,[ 22 23 24 ] further supporting the hypothesis that nausea was under-reported.…”
Section: Discussionsupporting
confidence: 75%
“…Surgery, chemotherapy, and radiotherapy are most commonly used for the treatment of BC. However, chemotherapeutic drugs generally have the disadvantages of being costly and causing side effects, including emesis, nausea, alopecia, myelosuppression, and thromboembolism [ 4 , 5 ]. Therefore, it is of considerable significance to identify safe, effective, and widely sourced anticancer drugs with limited side effects for the treatment of BC.…”
Section: Introductionmentioning
confidence: 99%
“…22,23 CTX has been used in the treatment of many tumors, such as prostate cancer and breast cancer. 24,25 Studies have shown that CTX can be used in the treatment of Rb. 26,27 Therefore, it is important to explore the role and mechanism of CTX in Rb progress.…”
Section: Discussionmentioning
confidence: 99%